The Existence of Islamic Institutions Through the Transformation of Education Digitalization at MTs Almaarif 01 Singosari - Ira Wirdatus Solichah; Ni'matuz Zuhroh (Universitas Muhammadiyah Enrekang, 2023)
transformation of digitalization of education which is growing rapidly. This digitalization technology brings new challenges to educational institutions so that they can compete with other educational institutions through learning modernization. Responding to this phenomenon, MTs Almaarif 01 Singosari as an Islamic-based school seriously contributes to planning sustainable learning by digitizing learning. The purpose of this research is to find out the existence of Islamic institutions in digitalization transformation through the Virtual Gallery innovation, as well as to analyze the obstacles and challenges that occur within them. This study uses a qualitative descriptive approach to process the data. The data collection techniques used included observation, document study of grades and student projects, literature studies, and interviews with teachers and students. The results of the study prove that digital transformation can help Islamic educational institutions maintain their existence in today's modern era. However, various problems were encountered in the implementation process such as students' difficulties using e-learning features, gaps in teachers' ability to use technology and differences in policies experienced by students